2007
DOI: 10.1093/ajcn/86.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal obesity and coronary artery calcification in young adults: the Coronary Artery Risk Development in Young Adults (CARDIA) Study

Abstract: Background: Whether abdominal obesity is related to coronary artery calcification (CAC) is not known. Objective: We investigated the relations of waist girth and waist-hip ratio (WHR) to CAC in 2951 African American and white young adults from the Coronary Artery Risk Development in Young Adults Study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 34 publications
5
59
0
3
Order By: Relevance
“…12 In another report, waist girth and waist hip ratio was associated with subclinical atherosclerosis measured by coronary calcium. 13 Importantly, in a large cohort of 1346 middle-aged Finnish men free of CVD at baseline followed for 10.6 years, waisthip ratio, WC and BMI were all directly associated with the risk of coronary events with waist-hip ratio providing additional information beyond BMI in predicting CHD, whereas BMI did not add to the prediction of CHD over waist-hip ratio. 14 Other studies have primarily focused on BMI as a predictor of CHD and/or all-cause mortality.…”
Section: Abdominal Obesity and Global Riskmentioning
confidence: 95%
“…12 In another report, waist girth and waist hip ratio was associated with subclinical atherosclerosis measured by coronary calcium. 13 Importantly, in a large cohort of 1346 middle-aged Finnish men free of CVD at baseline followed for 10.6 years, waisthip ratio, WC and BMI were all directly associated with the risk of coronary events with waist-hip ratio providing additional information beyond BMI in predicting CHD, whereas BMI did not add to the prediction of CHD over waist-hip ratio. 14 Other studies have primarily focused on BMI as a predictor of CHD and/or all-cause mortality.…”
Section: Abdominal Obesity and Global Riskmentioning
confidence: 95%
“…Reduction of body weight and decreasing the prevalence of obesity in society are critical health issues [25]. Research has shown that a relationship exists between abdominal obesity and subclinical atherosclerotic vascular disease in multiple race, sex and age groups.…”
Section: Resultsmentioning
confidence: 99%
“…Body size is another potentially confounding factor. Although higher body mass index is strongly associated with kidney stone formation (4) and greater vascular calcification (25)(26)(27), there are no data comparing weight or other measures of body size in stone formers with controls. Second, it is unclear whether the greater severity of abdominal aortic calcification in stone formers was independent of differences in bone mineral density between stone formers and controls.…”
Section: Division Ofmentioning
confidence: 99%